Core Assets Development in Software Product Lines - Towards a Practical Approach for the Mobile Game Domain - Nascimento, Leandro Marques do; Almeida, Eduardo Santana de; Meira, Silvio Romero de Lemos (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2009)
Software Product Lines (SPL) approaches are gradually being adopted as a powerful strategy for achieving high productivity and increasing quality in software engineering. A particular domain where the adoption of such approach may bring relevant benefits is the mobile game domain given the big diversity of handsets and the large number of commonalities among these games. However, applying SPL approaches in such domain is not trivial because of some restrictions, such as reduced memory and application size. In this context, this work presents a practical approach to implement core assets in a SPL in the mobile game domain combining good practices from previous work and briefly describing a case study performed with three mobile games.